Note Nitrogen Absorption Rate under Plasma Arc Compared to Resistance and Induction Melting - Sinha, O.P.; Gupta, R.C. (My University, 1994)
Nitrogen Absorption Rate under Plasma Arc Comparedto Resistance and Induction Melting
Keywords: Acoustic emissions; Induction melting; Plasma arc melting